Dynamics of Job Placement Matching Among Vocational High School Students in A Heterogeneous Regional Area: A Psychological Assessment-Based Analysis in Bogor Regency (2023–2025) - Wikan Putri Larasati; Mohamad Abdilah Nuradhi; Retno Pangestuti Widianti (International Journal of Science and Environment (IJSE), 2026)
The transition of Vocational High School (SMK) graduates into the labor market constitutes a strategic challenge within Indonesia’s workforce development policy, particularly at the regional level. This study analyzes the dynamics of job placement matching among SMK students in Kabupaten Bogor during the 2023–2025 period using secondary data derived from the Job Placement Assessment implemented under national labor policy. The assessment measures psychological readiness across seven dimensions and generates recommendations for domestic employment, overseas employment, and entrepreneurship. Using a quantitative descriptive design with a limited longitudinal perspective, this study examines year-to-year changes in the distribution of job placement recommendations. The results show that while the psychological readiness profiles of SMK students remain relatively stable over the observed period, job placement outcomes experience significant shifts. Recommendations for domestic employment decline, whereas recommendations for overseas employment and entrepreneurship increase. These findings indicate that changes in job placement outcomes are primarily driven by structural and contextual labor market dynamics rather than by changes in individual readiness. The study underscores the importance of integrating psychological assessment data with regional labor market analysis to support adaptive career counseling, targeted workforce planning, and region-specific employment policies. By emphasizing the need for longitudinal and territorial interpretation of assessment outcomes, this research contributes to evidence-based policymaking in vocational education and labor market governance.